PEMBATALAN HIBAH OLEH PENGADILAN AGAMA - Dhofir Catur Bashori; Miftahul Ichsan (JURNAL HAKAM, 2021)
A grant is a gift made by someone to another party that is carried out while still alive and its implementation is carried out while the grantor is still alive. Grants in any law are basically irrevocable, but if certain conditions are met the grant can be cancelled. This study aims to determine that the decision to cancel the grant made by the Situbondo Religious Court in case number 0374/Pdt.G/2017/PA.Sit was in accordance with applicable legal provisions or not, to determine whether the cancellation of the grant made by the Religious Court was allowed or not. not in fiqh. Based on this research, the results obtained: first, the cancellation of the grant made at the Situbondo religious court in accordance with the applicable legislation, the legal basis for the judge's assembly to decide the case was because the grant did not meet the requirements of the grant. Second, the cancellation of grants made by religious courts is allowed in fiqh.